Arabidopsis Heterotrimeric G-protein Regulates Cell Wall Defense and Resistance to Necrotrophic Fungi - Delgado Cerezo, Magdalena; Sánchez Rodríguez, Clara; Escudero, Viviana; Miedes, Eva; Fernández, Paula Virginia; Jordá, Lucía; Hernández Blanco, Camilo; Sánchez Vallet, Andrea; Bednarek, Pawel; Schulze-Lefert, Paul; Somerville, Shauna; Estevez, José Manuel; et al. (My University, 2024)
The Arabidopsis heterotrimeric G-protein controls defense responses to necrotrophic and vascular fungi. The agb1 mutant impaired in the Gb subunit displays enhanced susceptibility to these pathogens. Gb/AGB1 forms an obligate dimer with either one of the Arabidopsis Gg subunits (g1/AGG1 and g2/AGG2). Accordingly, we now demonstrate that the agg1 agg2 double mutant is as susceptible as agb1 plants to the necrotrophic fungus Plectosphaerella cucumerina. To elucidate the molecular basis of heterotrimeric G-protein-mediated resistance, we performed a comparative transcriptomic analysis of agb1-1 mutant and wild-type plants upon inoculation with P. cucumerina. This analysis, together with metab olomic studies, demonstrated that G-protein-mediated resistance was independent of defensive pathways required for resistance to necrotrophic fungi, such as the salicylic acid, jasmonic acid, ethylene, abscisic acid, and tryptophan-derived metabolites signaling, as these pathways were not impaired in agb1 and agg1 agg2 mutants. Notably, many mis-regulated genes in agb1 plants were related with cell wall functions, which was also the case in agg1 agg2 mutant. Biochemical analyses and Fourier Transform InfraRed (FTIR) spectroscopy of cell walls from G-protein mutants revealed that the xylose content was lower in agb1 and agg1 agg2 mutants than in wild-type plants, and that mutant walls had similar FTIR spec tratypes, which differed from that of wild-type plants. The data presented here suggest a canonical functionality of the Gb and Gg1/g2 subunits in the control of Arabidopsis immune responses and the regulation of cell wall composition. Key words: Plant immunity; cell wall; indole glucosinolates; xylose; necrotropic fungi; G-protein